COAL MINE DETECTION MONITORING AND COMPUTING USING IOT - Jitendra, Ladi; Baskar, Radhika (International Journal of Psychosocial Rehabilitation, 2020)
Safety in the mining process is needed to save a number of human’s lives. The coal mining is deployed in the areas where a large amount of coal is extracted. So at the period of mining, the monitoring of the various parameters using the sensors. In this paper, they propose the monitoring of the light detection, leakage of the gas, temperature, and humidity. The sensors are connected to the controller. When the sensor range is exceeded above the threshold value, the buzzer will be ON to give the alert message. A LDR sensor is used, which can sense the presence of light. All the sensor data are updated in the IOT. The WIFI module is used in transmitting and receiving the data in the clouds. The data are plotted in the form of graphs at each interval of time the cloud data is updated. The data communication to the cloud occurs at the baud rate of 115200. This method can be helpful in saving the employees in a dangerous situation.